(untitled) (Research, Society and Development, 2023)
More than 16 million people are toothless in Brazil. Brazilian dental care currently takes place in several sectors (primary care, secondary care and tertiary care) such as Basic Health Units (UBS) and Dental Specialties Center (CEO), which is a service offered by the Unified Health System (SUS). This study aims to describe the perception of the student during the internship in oral health within a Basic Health Unit (UBS), located in the capital Palmas – TO, through an experience report with dental care. To this end, we opted for the methodology of experience reporting, where through a cross-sectional evaluation methodology, the experiences within the hourly load of the semester are reported. The supervised internship works as a space for integration in practice between teaching and health services, adding an opportunity for academics to experience in practice the reality in public care and obtain professional experience. In colleges you have the best for the patient in technological and innovative issues unlike the UBS that professionals perform procedures in the best way they have available to them. With this experience it was clarified that the SUS, although fragile is an example of health for the country, covering the entire population. The internships were offered unique and fantastic opportunities, transforming the perception of the student’s vision and providing a personal and academic growth, in experiencing the public reality, which a theory cannot achieve.